VITAMIN D DEFICIENCY DID NOT AUGMENT THE PROGRESSION OF HIGH-FRUCTOSE-INDUCED NONALCOHOLIC FATTY LIVER DISEASE IN RATS - İlknur Bingül; Canan Küçükgergin; Abdurrahman Fatih Aydın; Asiye Işın Doğan Ekici; Semra Doğru Abbasoğlu; Mehmet Müjdat Uysal (İstanbul Tıp Fakültesi Dergisi)
Objective: Vitamin D has antioxidant, anti-inflammatory and antiglycation activities, and hepatoprotective potential. There is a relationship between vitamin D deficiency (VDD) and the severity of liver disorders. VDD has been proposed to contribute to the progression of nonalcoholic fatty liver disease (NAFLD). However, experimental results are not clear. Therefore, in this study, the effects of a VDD diet on high fructose (HFr) drinking-induced NAFLD was evaluated. Material and Method: Male Wistar rats were divided into four groups as control, HFr, VDD+HFr, and VDD. Control and HFr groups were fed a control diet, and other groups with a VDD-diet for 12 weeks. HFr (30%; w/v; in drinking water) was given in the last 8 weeks. Insulin resistance (IR), serum lipids, hepatic triglyceride, lipid peroxide, protein carbonyl, advanced glycation end products (AGEs) and inflammation (TNF-α and myeloperoxidase) parameters, and histopathological changes were investigated. Results: Increases in serum transaminases, hypertriglyceridemia, and IR were observed in HFr and VDD+HFr groups. Increased liver triglyceride, lipid and protein oxidation products, protein glycation and inflammation markers as well as microvesicular hepatic steatosis and hepatocyte ballooning were observed in both groups. Although IR and hepatic inflammation markers were higher in the VDD+HFr group, serum transaminases, hepatic triglyceride, lipid and protein oxidation products, and glycation indicators in the liver did not alter between the two groups. However, Nrf2 mRNA expression and superoxide dismutase andglutathione peroxidase mRNA expression and activities were significantly higher in the VDD+HFr group. Conclusion: Our results show that VDD did not augmented HFr-induced hepatotoxicity and glycooxidative stress in the liver of rats.